Women’s Knowledge, Perceptions, And Potential Demand Towards Caesarean Section - Ajeet Saoji; Jaydeep Nayse; Nandkishore Kasturwar; Nisha Relwani (National Journal of Community Medicine, 2011)
In today’s situation when the access to obstetric care is growing day by day there has been a concern over the rising caesarean rates over the world. A cross-sectional study was undertaken with an objective to determine the level of knowledge, attitudes, and perceptions about CS among pregnant women. All pregnant women, attending antenatal clinic, were interviewed with a structured questionnaire. Data analysis was done by using Epi info software. Of the total 247 women, participated in this study, the potential demand for CS was low and majority of women preferred vaginal delivery (91.5%). The majority of women (65.1%) were found to have very little knowledge. Overall, women preferring caesarean birth were multiparous (P<0.05), and were more likely to have had previous caesarean delivery (P<0.001), but there were otherwise no differences in age, parity, income, or education. However, most are still in favor of CS if it is necessary to protect their health or that of their infant. Study also revealed that there is need to provide better information for pregnant women during the antenatal period about modes of delivery, their indications, advantages and adverse consequences which will enable them to make an informed decision.